If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -19n + 12 = -15n + -12 Reorder the terms: 12 + -19n = -15n + -12 Reorder the terms: 12 + -19n = -12 + -15n Solving 12 + -19n = -12 + -15n Solving for variable 'n'. Move all terms containing n to the left, all other terms to the right. Add '15n' to each side of the equation. 12 + -19n + 15n = -12 + -15n + 15n Combine like terms: -19n + 15n = -4n 12 + -4n = -12 + -15n + 15n Combine like terms: -15n + 15n = 0 12 + -4n = -12 + 0 12 + -4n = -12 Add '-12' to each side of the equation. 12 + -12 + -4n = -12 + -12 Combine like terms: 12 + -12 = 0 0 + -4n = -12 + -12 -4n = -12 + -12 Combine like terms: -12 + -12 = -24 -4n = -24 Divide each side by '-4'. n = 6 Simplifying n = 6
| 42=-7y | | 11=u-7 | | 2.5h=80 | | 11-12b=3 | | 4u+8=5u+3 | | 2.5=80 | | 4x=3x-7 | | 3y-y=4-18 | | 5t^2-8t=3 | | -3=7y | | -3v=-18 | | 5-8x=55-22x | | 6=v+15 | | -9+14=-2u+7u | | -0.625+m=0.333334 | | -6v-6v=-7-18 | | 7v-1=6v-6 | | 4x+33=14x-77 | | 30X-6=4 | | 5x^3-2=x-x^2 | | 4+3=-2w-3w | | x^2+4x+10=3 | | 7(2x-4)=2x+8 | | 5x+3=4x+4 | | -4+3y=3+1 | | 2x-13=109 | | 4+2=w+7w | | 4w-4=5w-1 | | -17-15=-8y+4y | | 2+3=12 | | 7m-20=3m | | 32x+43-20x=-25+30-45x |